Empowering Sinar Harapan UMKM Coconut Processing and E-Commerce Development in Bongohulawa Village, Gorontalo: Empowering Sinar Harapan UMKM Coconut Processing and E-Commerce Development in Bongohulawa Village, Gorontalo - Kartika Chandra Pelangi; Abd Rahmat Karim Haba; Nurhayati Olii; Zohrahayaty (LP2M INSURI Ponorogo, 2025)
The Sinar Harapan MSME in Bongohulawa Village has been producing coconut oil due to its easy availability and its conventional sales system. The number of members of the Sinar Harapan MSME is 20. With this program, the membership of Sinar Harapan MSME is expected to increase in the future due to advancements in production and sales systems. The specific purpose of this community service is to develop e-commerce-based marketing strategies and expand market reach. The method used in this service involves training and mentoring on the e-commerce system's processing. The results obtained from this service are based on a questionnaire completed by 100 participants, which indicates that 83% of respondents strongly agree with the quality of the coconut oil produced.